Pin, pin, sarabín - Ada, Alma Flor.; Torrecilla, Pablo (New York : Scholastic, 1995)
Every afternoon the neighborhood children of various ethnic and social backgrounds gather to play and sing traditional nursery rhymes in the town's park.
Keywords: Play -- Fiction; Games -- Fiction; Spanish language materials